A Practical Approach to Developing and Using Online Games for Transdisciplinary Research into Complex Social-Ecological Systems - Valero, Diana E.; McKeon, C. Rose; Bussière, Luc; Corniani, Natália; Colmenarez, Yelitza C.; Hodgson, Isla; Mangan, Rosie; Polanczyk, Ricardo A. [UNESP]; Tinsley, Matthew; Bunnefeld, Nils (Taylor & Francis, 2025)
Research games provide a promising avenue for studying social-ecological systems because they can capture complexity and reflect multiple stakeholders’ perspectives. However, there are few methodological studies on the design, validation and implementation of research games. This paper focuses on the development and implementation of an online multi-player game representing the social-ecological system underlying farmers’ decision-making. We detail three key aspects of spatially explicit game development: design, validation and game sessions. Our approach provides new integration of social science ecology and practice knowledge using informed-design elements, and demonstrates mediated fieldwork with community mobilizers and personal smartphones. We also provide practical suggestions for scaling-up games to increase the number and diversity of participants and the spatial scale of social-ecological research.
Keywords: Co-design; game methods; land management; pest resistance; research games